Genetic association studies of ACE and PAI-1 genes in women with recurrent pregnancy loss - Su, Mei-Tsz; Lin, Sheng-Hsiang; Chen, Yi-Chi; Kuo, Pao-Lin (Thrombosis and Haemostasis, 2013)
A fine balance between coagulation and fibrinolysis is critical in early pregnancy. Plasminogen activator inhibitor-1 (PAI-1) and angiotensin converting enzyme (ACE) are involved in the fibrinolytic process, and several studies have reported the association between their gene polymorphisms and recurrent pregnancy loss (RPL). This study was conducted to investigate the association between PAI-1 and ACE polymorphisms and idiopathic RPL, using meta-analyses. A systematic review of the published literature from the MEDLINE and EMBASE databases before April 2012 was conducted. Of 209 potentially relevant studies, 22 case-control studies comprising a total of 2,820 RPL patients and 3,009 controls were included. Among these studies were 11 reports of PAI-1 4G/5G and 11 of ACE I/D polymorphisms in patients with RPL. A significant association was found withthe ACE I/D polymorphism [summary odds ratio 1.29 (95% confidence interval 1.02–1.62)] in studies including more than two recurrent abortions. Subgroup analysis did not show significant associations with RPL in Caucasian and non-Caucasian patients. Meta-analyses of PAI-1 4G/5G polymorphism were not found associations with RPL in studies including more than two or three recurrent abortions, and in studies of Caucasian and non-Caucasian patients. In conclusion, meta-analyses showed a significant association between the ACE I/D polymorphism and idiopathic RPL. High clinical heterogeneity existed among studies of PAI-1 4G/5G, and the aggregated data failed to confer higher susceptibility to idiopathic RPL. More well-designed studies with different ethnic populations are required for future integration.
Keywords: Meta-analysis; fibrinolysis; coagulation; ACE; PAI-1; recurrent pregnancy loss